Social Media Analysis On Malang Specialty Food Msmes - Asri, Tri Mega (Universitas Telkom, 2025)
It will be seen throughout social media that the potential of MSMEs in Indonesia is very large to develop. However, MSME players unfortunately are still not responsive to change toward digitalization or online. The development of MSMEs has experienced several problems, one of which is marketing problems, especially related to branding through social media, particularly Instagram. This study aims to obtain a mapping picture of the problems faced by MSMEs when developing branding faced in the use of Instagram social media. The target MSMEs in this study are MSMEs of superior products, namely specialty foods located in Malang and its surroundings, which have Instagram social media accounts and high followers. The analysis was carried out using qualitative and quantitative descriptive approach.